Maggie: Alaska's Last Elephant - Curtis, Jennifer Keats; Saroff, Phyllis V. (Mt. Pleasant Arbordale Publishing, 2018)
"Elephants are social animals. Maggie and Annabelle used to live together at the Alaska Zoo. But after Annabelle died, Maggie was all alone. For years, zookeepers tried to keep her happy (and warm). But ultimately they sent Maggie to live at a sanctuary (PAWS). Now she is happy and at home with her new herd of other elephants. This is a heartwarming story of how zoos ensure the best for the animals in their care--even if the best is not at their zoo."--Inside dust jacket.
620L
Decoding demand: 81 (very high)
Semantic demand: 92 (very high)
Syntactic demand: 90 (very high)
Structure demand: 82 (very high)
Accelerated Reader AR
Keywords: Elephants -- Juvenile literature; Elephants -- Behavior; Juvenile literature; Zoo animals -- Behavior; Juvenile literature; Elephants; Elephants -- Behavior; Zoo animals